Escrow Suatu Perjanjian Pengantaran - Pandika, Rusli (LAW REVIEW, 2002)
Escrow is an agreement to establish an impartial and trustworthy intermediary to collect, Â to clarify and to keep documents, commercial paper, valuable goods and/or money to be Â hand over to the party or parties in accordance with the conditions set forth in the escrow agreement. Escrow may take a substantial role to support the implementation of various transactions. Indonesian contract law is accommodative to the formation of an escrow-like agreement. The functions and purposes of escrow are substantially acceptable to Indonesian legal system.Â